(3LhGgQ GdcdGe TQM TQGFY GdESdGes - (3GdfLaj, eMeO GdfLaj, eMeO MSf Hf HGbQ, J (B1266(3g` (B1850(3es
(3ChdgG (B:s
(3ChdgG(B: (3ef GdNdjbI aj bhdg JYGdi(B: (3jG OGhO EfG LYdfGc NdjaI, hHd hef GdMce aj bhdg JYGdi(B: (3hBJjfGg GdMce UHjG, bGd CejQ GdeDefjf Ydjg GdSdGe dTQjM(B: (3bO LdSJ eLkSG dG jLdSg EdG fHj Ch hUjs
(3BNQgG (B:s
(3BNQgG(B: (3hdcf GdCbhi eG YQaJ gPG hHbjJ eSGFd ePchQI aj cJH GdYGeI hGdNGUI JQcfG GdJYQV dgG JQLjkMG ddGTJZGd HGdCge efgG heNGaI GdJWhjd hdcf GdCeQ ajgG gjf dCf GdeQLY ajgG GdbhGYO GdYGeI hdG fU ajgG HGdNUhUs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 214s
(3GdPQjYI, L (B5: 196s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis